2015
DOI: 10.1097/md.0000000000002139
|View full text |Cite
|
Sign up to set email alerts
|

Correlation Between Residual Displacement and Osteonecrosis of the Femoral Head Following Cannulated Screw Fixation of Femoral Neck Fractures

Abstract: The aim of the study was to introduce a new method for measuring the residual displacement of the femoral head after internal fixation and explore the relationship between residual displacement and osteonecrosis with femoral head, and to evaluate the risk factors associated with osteonecrosis of the femoral head in patients with femoral neck fractures treated by closed reduction and percutaneous cannulated screw fixation.One hundred and fifty patients who sustained intracapsular femoral neck fractures between … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(14 citation statements)
references
References 19 publications
0
11
0
1
Order By: Relevance
“…Of the 16 included studies, 4 reported [16, 19, 26, 33] the correlation between gender and ONFH after IFFNF. Because of nonsignificant heterogeneity among the studies, the fixed effect model was utilized ( I 2 = 25%, P = 0.26).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Of the 16 included studies, 4 reported [16, 19, 26, 33] the correlation between gender and ONFH after IFFNF. Because of nonsignificant heterogeneity among the studies, the fixed effect model was utilized ( I 2 = 25%, P = 0.26).…”
Section: Resultsmentioning
confidence: 99%
“…Data on age were available for the meta-analysis from 4 studies [16, 17, 19, 28], and nonsignificant heterogeneity was presented among the studies ( I 2 = 17%, P = 0.31). Therefore, the fixed effect model was applied.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Keinesfalls sollte eine im Valgus impaktierte Fraktur während der Operation disloziert und somit destabilisiert werden -die Osteosynthese erfolgt in situ. Vor einer zu starken Valgisierung unter der Operation sei gewarnt, da diese mit einem erhöhten Hüftkopfnekroserisiko vergesellschaftet ist (2,12). Dislozierte mediale Schenkelhalsfrakturen (Garden-Typen III und IV) sollten nur bei jungen Patienten exakt reponiert und einer Osteosynthese zugeführt werden, um das Hüftgelenk zu erhalten.…”
Section: Therapie Der Medialen Schenkelhalsfrakturunclassified
“…Avascular necrosis of the femoral head and nonunion of fractures are the two major complications in the therapy of femoral neck fractures. The optimal treatment method of femoral neck fractures is manual reduction and internal fixation, and the healing rate is 80% to 90%. Therefore, the treatment principle of femoral neck fractures is early non‐traumatic reduction, reasonable multiple nail fixation, and early recovery.…”
Section: Introductionmentioning
confidence: 99%